2021
DOI: 10.1371/journal.pone.0250874
|View full text |Cite
|
Sign up to set email alerts
|

A mixture of quebracho and chestnut tannins drives butyrate-producing bacteria populations shift in the gut microbiota of weaned piglets

Abstract: Weaning is a critical period for piglets, in which unbalanced gut microbiota and/or pathogen colonisation can contribute to diseases that interfere with animal performance. Tannins are natural compounds that could be used as functional ingredients to improve gut health in pig farming thanks to their antibacterial, antioxidant, and antidiarrhoeal properties. In this study, a mixture of quebracho and chestnut tannins (1.25%) was evaluated for its efficacy in reducing the negative weaning effects on piglet growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…The analysis of the fecal microbiota profile revealed 938 OTUs identified at the genus level among all of the samples. From a taxonomic point of view, our results on phyla, families, and genera composition (Figure 2) are generally comparable with those reported in other studies [20,[26][27][28]. The alpha diversity analysis of the bacterial community suggested that the co-feed treatment affected some indices, with the Shannon and Simpson values being statistically significant between the feeding conditions (Figure 1B,C).…”
Section: Discussionsupporting
confidence: 90%
“…The analysis of the fecal microbiota profile revealed 938 OTUs identified at the genus level among all of the samples. From a taxonomic point of view, our results on phyla, families, and genera composition (Figure 2) are generally comparable with those reported in other studies [20,[26][27][28]. The alpha diversity analysis of the bacterial community suggested that the co-feed treatment affected some indices, with the Shannon and Simpson values being statistically significant between the feeding conditions (Figure 1B,C).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the relative abundance of Olsenella , Romboutsia , Sharpea , and Clostridium_sensu_stricto_1 also increased due to amylopectin infusion. Clostridium_sensu_stricto_1 , Olsenella , and Sharpea could provide energy for intestinal cells and protect the gut barrier and are seen as butyrate-producing bacteria ( 36 38 ). Romboutsia is believed to play an important role in gut microbiota dysbiosis and cardiac dysfunction; it has also been positively correlated with indole derivatives, which are harmful metabolites of protein fermentation ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among SCFAs effective in metabolic syndrome, butyric and propionic acids are selected and measured by the HPLC method. Considering that Akkermansia and Butyrivibrio are known as two of the bacteria that produce the above metabolites [ 47 , 51 ], the results of this section can be used indirectly in the cross-validation of the previous part, "Effect of exercise on intestinal microbial content". In addition, these results can help us find the impact of diabetes and exercise interventions on the concentration of SCFAs in the intestinal tissue.…”
Section: Resultsmentioning
confidence: 99%